What Makes Whistleblowers So Threatening?; Comment on "Cultures of Silence and Cultures of Voice: The Role of Whistleblowing in Healthcare Organisations" - Charles Frederick Alford (Kerman University of Medical Sciences, 2016)
Whistleblowing is defined by the retaliation that those who speak out receive. Why some organizations find it almost impossible not to retaliate depends more on the properties of the organization than the act of the individual whistleblower. These properties are, to greater or lesser degree, present in all organizations. Not all organizations retaliate against whistleblowers, but the whistleblower represents a threat to every organization. And to every individual within the organization, because the whistleblower challenges the morality and ethics of the rest of us.